2021
DOI: 10.1111/dth.14747
|View full text |Cite
|
Sign up to set email alerts
|

Association between rosacea and smoking: A systematic review and meta‐analysis

Abstract: Rosacea is a chronic inflammatory disease of the centrofacial region. However, the association between rosacea and smoking remains controversial. To evaluate the association between rosacea and smoking, we performed a systematic review and meta-analysis. A comprehensive systematic search of literature published before October 15, 2020 on online databases (including Web of Science, PubMed, Cochrane Library, and Embase) was performed. The pooled odds ratios (ORs) were calculated. 12 articles were included, cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…The risk of the disease in active smokers was lower than in the general population, while it was higher in people who quit smoking. Maculopapular and hypertrophic types were more often observed in smokers [34].…”
Section: Dietamentioning
confidence: 88%
See 1 more Smart Citation
“…The risk of the disease in active smokers was lower than in the general population, while it was higher in people who quit smoking. Maculopapular and hypertrophic types were more often observed in smokers [34].…”
Section: Dietamentioning
confidence: 88%
“…U aktywnych palaczy ryzyko rozwoju choroby było mniejsze od populacyjnego, natomiast zwiększone u osób, które zaprzestały palenia. U palaczy częściej obserwowano typ grudkowo-krostkowy oraz przerostowy [34].…”
Section: Palenie Tytoniu a Trądzik Różowatyunclassified
“…These controversial ndings can be explained by the microvascular constriction caused by the nicotine in tobacco (43). To be noted, based on a systematic review and meta-analysis conducted in 2020, this protective effect of current smoking on the risk of rosacea may be temporary (44). Regarding the severity of the disease, Alinia et al reported a signi cant relationship between the severity of rosacea and number of cigarettes smoked in patients who had quit smoking (45).…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study in the U.K. reported that smoking was associated with a substantially reduced risk of developing rosacea ( 5 ). Furthermore, a recent meta-analysis demonstrated that current smoking was associated with a decreased risk of rosacea ( 6 ). However, a study conducted in Turkey presented contradictory findings, they reported a significantly higher risk of developing rosacea, particularly the erythema of subtype 1 rosacea, among smokers ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies are likely attributed to the inherent limitations of observational studies, including the non-randomized design, residual confounding, and the possibility of reverse causation. For example, the above-mentioned meta-analysis on smoking and rosacea risk primarily used case-control studies, which may be susceptible to recall bias in the included data ( 6 ). Additionally, it is worth noting that the largest study included in the meta-analysis was conducted among patients on antihypertensives, which could potentially introduce bias in the assessment of rosacea cases.…”
Section: Introductionmentioning
confidence: 99%